2016
DOI: 10.1179/1476830514y.0000000158
|View full text |Cite
|
Sign up to set email alerts
|

The role of IgG hypersensitivity in the pathogenesis and therapy of depressive disorders

Abstract: Depressive episodes are associated not only with changes in neurotransmission in the central nervous system, but also may lead to structural changes in the brain through neuroendocrine, inflammatory, and immunological mechanisms. The aim of this article is to present a new hypothesis connecting the inflammatory theory of depression with IgG food hypersensitivity and leaky gut syndrome. This new potential pathway that may mediate the pathogenesis of depression implies the existence of subsequent developmental s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 108 publications
0
20
0
Order By: Relevance
“…The so‐called gut–brain axis, linking emotional and cognitive brain centers with gastrointestinal function, has recently received substantial attention in relation to psychiatric disorders . This bidirectional crosstalk between the digestive system and the brain could be mediated via changes in gut microbiota resulting in immune activation, potentially generating various types of psychiatric symptoms . Specifically, a leaking gut allows translocation of lipopolysaccharides (LPS), molecules found on the outer membrane of gram‐negative bacteria, from the gut into the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…The so‐called gut–brain axis, linking emotional and cognitive brain centers with gastrointestinal function, has recently received substantial attention in relation to psychiatric disorders . This bidirectional crosstalk between the digestive system and the brain could be mediated via changes in gut microbiota resulting in immune activation, potentially generating various types of psychiatric symptoms . Specifically, a leaking gut allows translocation of lipopolysaccharides (LPS), molecules found on the outer membrane of gram‐negative bacteria, from the gut into the circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is some recent evidence linking major depressive disorder to celiac disease or gluten sensitivity (7,8), the evidence does not have the long history and series of replications found in the literature on schizophrenia (9). We agree with the authors of the letter that celiac disease has been associated with psychiatric disorders other than schizophrenia, including major depressive disorder.…”
Section: Response To Dell'osso and Ellimentioning
confidence: 64%
“…On the one hand, a possible cause of the hyperreactivity among patients with MDD may be disruption of gut-microbiome-brain axis, which is related to low-grade inflammation occurring peripherally and in the CNS [ 19 ]. It is suggested that altered gut microbiota could be responsible for increased gut permeability.…”
Section: Discussionmentioning
confidence: 99%
“…A scenario proposed by Karakula-Juchnowicz et al that links the inflammatory theory of depression with IgG food hypersensitivity and leaky gut syndrome assumes that loss of integrity of the tight-junction barrier could be caused by food antigens [ 19 ]. Overproduction of zonulin triggered, for example, by gliadin through activation of the epidermal growth factor receptor and protease-activated receptor causes loosening of the tight junction barrier and an increase in permeability of the gut wall.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation